Collembola dan Konservasi Tanah Berkelanjutan: Review atas Wawasan dari Scopus AI - Husamah, H.; Rahardjanto, Abdulkadir; Permana, Tutut Indria (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
Collembola or springtails, as an important but often overlooked component of soil biota, it plays an important role in nutrient cycles and soil stability. This article aims to analyze Collembola's role in soil health and ecosystem services, the impact of agricultural practices on their communities, sensitivity to environmental changes, and management recommendations based on Scopus AI-indexed data. The method used is a systematic literature review utilizing natural language and keyword search features from Scopus AI to gather relevant literature. The results of the study show that Collembola significantly contributes to organic matter decomposition, soil quality improvement, and erosion control. Additionally, conservation tillage practices and organic amendments have been shown to enhance Collembola species diversity. In conclusion, Collembola plays a key role in sustainable soil conservation, but further research is needed to understand the impact of climate change and agricultural practices on their ecological functions. This study also offers recommendations for more effective management strategies to support soil sustainability.